(untitled) (Al-Mithaq ( Research Journal of Islamic Theology), 2024)
The main aim of this research manuscript is to explore the significance of teaching as a profession in the field of education leading to progress in all fields of life. The cream of a nation must enthusiastically adopt this profession if that nation aspires to develop by leaps and bounds. This profession can be adopted by the cream if it is made lucrative by awarding great respect to it, outstanding monetary / French benefits and state patronage as it was done by Prophet Muhammad (ﷺ) and his successors particularly the Rightly Guided caliphs in the early stage of the Muslim state. Therefore, Muslims surpassed other nations, progressed tremendously and Islam reached far flung areas of the world. So, the way to social, economic and political advancement in all walks of life is paved by the investment and development in education particularly in teachers by motivating the cream of a nation to prefer the sacred profession of teaching.